Water Quality as a Potential Factor Influencing Seagrass Change Over Time at Cahuita National Park, Costa Rica - Samper Villarreal, Jimena (2021)
We measured water temperature, salinity, Secchi, and concentrations of dissolved oxygen, chlorophyll, suspended matter, and nutrients in the water column at six sites at Cahuita National Park on the southern Caribbean coast of Costa Rica, at three-month intervals over a two-year time period in 2017 and 2018. We also assemble and compare the available water quality measurements for the area dating back to 1979. Water quality conditions were similar to previous reports at this site and nearby areas, with the exception of decreased suspended matter, and increased nitrogen concentrations. Higher nitrogen concentrations at this location may be the result of the growing human population, and may be a factor influencing seagrass decline over time, although the observed concentrations are considered adequate for seagrass development. We recommend continued monitoring of seagrasses and water quality at this location, along with adequate effluent and catchment management.